الأمن الطاقوي في الجزائر: الرهانات والتحديات - مومن, عواطف (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
يعتبر الأمن الطاقوي من المضامين الجديدة للأمن لفترة ما بعد الحرب الباردة، و يشكل رهانا أساسيا من رهانات الأمن الشامل، فأصبح التحول نحو الطاقة المتجددة والنظيفة مطلبا ملحا لدى معظم دول العالم، والجزائر على غرار كل دول العالم أولت اهتماما كبيرا بموضوع الأمن الطاقوي لضمان أمنها القومي في ظل الرهانات والتحديات الراهنة، بحيث تزخر الجزائر بمصادر طبيعية هائلة لإنتاج الطاقات المتجددة البديلة عن مصادر الطاقة الأحفورية، حيث قامت الجزائر بتطوير السياسات الطاقوية تبعًا للتطور الحاصل في قطاع الطاقة داخليا وخارجياً، إضافةً إلى الاهتمام المتزايد بالطاقات المتجددة ومحاولة تطويرها لتأخذ نصيبها من الاستهلاك المحلي الذي ما فتئ يتزايد بشكل كبير منذ سنة 1999م، وذلك كله من أجل تكريس وتحقيق الأمن الطاقوي الجزائري وبالتالي الأمن القومي. The Energy security is one of the new contents of security for the post-Cold War period, and it constitutes a fundamental bet from the bets of comprehensive security. The shift towards renewable and clean energy has become an urgent requirement for most countries of the world, and Algeria, like all countries of the world, has paid great attention to the issue of energy security to ensure its national security in light of the current stakes and challenges, even Algeria is rich in tremendous natural resources to produce renewable energies alternative to fossil energy sources, as Algeria has developed energy policies according to the development in the energy sector internally and externally, in addition to the growing interest in renewable energies and trying to develop them to take their share of domestic consumption that is increasing Significantly since 1999, all in order to consecrate and achieve Algerian energy security and thus national security.